(untitled) (Eurasian Journal of Philology Science and Education, 2015)
Article is devoted to a problem of studying of the anthem from the historical, musical and culturological point of view, to studying of terminology and etymology, detection of specific features, its value, a role, emergence. The development evolution history, a historical way of formation, fixing to itself of one of many kinds of a song genre is looked through, the comparative analysis on the example of anthems of India and Kazakhstan and also in comparison with mass Kazakh national songs is provided. This article is attempt to consecrate these or those problems of the studying connected with the anthem to bring new understanding about a song genre – the anthem.